1880 Me. Laws 212-213 - (:unkn) unknown (My University, 1880)
An Act to Punish Tramps, ch. 213, §§ 1-2: Any tramp who shall enter any dwelling house, or kindle any fire in the highway or on the land of another, without the consent of the owner or occupant thereof, or shall be found carrying any fire-arm or other dangerous weapon, or shall threaten to do any injury to any person, or to the real or personal estate of another, shall be punished by imprisonment at hard labor in the state prison not more than two years."
Keywords: CARRY - DANGEROUS PERSONS